Migration and the labour market impacts of COVID-19 - Nathan Barker; C. Austin Davis; Paula López-Pe\~na; Harrison Mitchell; Ahmed Mushfiq Mobarak; Karim Naguib; Maira Emy Reim\~ao; Ashish Shenoy; Corey Vernot (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Using detailed microdata, we document how migration-dependent households are especially vulnerable during the COVID-19 pandemic. We create pre- and post-COVID panel datasets for three populations in Bangladesh and Nepal, leveraging experimental and observational variation in prior migration dependence. We report 25 per cent greater declines in earnings and fourfold greater prevalence of food insecurity among migrant households since March. Causes include lower migration rates, less remittance income per migrant, isolation in origin communities, and greater health risks. We compile a large set of secondary data to demonstrate the extent of vulnerability worldwide and conclude with recommendations for policy targeted at migrants.
Keywords: O15; J61; I32; 330; migration; COVID-19; panel; Bangladesh; Nepal